2015
DOI: 10.1080/00273171.2014.977429
|View full text |Cite|
|
Sign up to set email alerts
|

Detecting Misspecified Multilevel Structural Equation Models with Common Fit Indices: A Monte Carlo Study

Abstract: This study investigated the sensitivity of common fit indices (i.e., RMSEA, CFI, TLI, SRMR-W, and SRMR-B) for detecting misspecified multilevel SEMs. The design factors for the Monte Carlo study were numbers of groups in between-group models (100, 150, and 300), group size (10, 20, 30, and 60), intra-class correlation (low, medium, and high), and the types of model misspecification (Simple and Complex). The simulation results showed that CFI, TLI, and RMSEA could only identify the misspecification in the withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
103
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(116 citation statements)
references
References 41 publications
11
103
2
Order By: Relevance
“…Hsu et al (2015) found ICC had no substantial impact on the effectiveness of traditional fit indices. The major reason that Hsu et al (2015) did not find ICC as an important factor is that the traditional single-level fit indices were the main focus and the performance of these traditional fit indices was in general overpowered by the within-level model misspecification.…”
Section: The Role Of Icc In the Performance Of Traditional And Level-mentioning
confidence: 91%
See 1 more Smart Citation
“…Hsu et al (2015) found ICC had no substantial impact on the effectiveness of traditional fit indices. The major reason that Hsu et al (2015) did not find ICC as an important factor is that the traditional single-level fit indices were the main focus and the performance of these traditional fit indices was in general overpowered by the within-level model misspecification.…”
Section: The Role Of Icc In the Performance Of Traditional And Level-mentioning
confidence: 91%
“…Our study extended this line of research specifically by furthering Hsu et al's (2015) study with the focus on how the effectiveness of ''level-specific'' fit indices is affected by varying ICC values. We aim to provide better understanding of the utilization of level-specific fit indices in MSEM given data with different levels of ICC, which has not yet been thoroughly investigated in previous level-specific fit index studies.…”
Section: Introductionmentioning
confidence: 95%
“…We evaluated the models based on the Comparative Fit Index (CFI; Bentler, 1990), root mean square error of approximation (RMSEA; Steiger & Lind, 1980), the standardized root mean square residual for the within-level (i.e., individual-level) model (SRMR-within; Hu & Bentler, 1999), and the standardized root mean square residual for the between-level (i.e., team-level) model (SRMR-between;Hsu, Kwok, Lin, & Acosta, 2015). The model with an adequate fit should have CFI greater than 0.90, RMSEA less than 0.06, SRMR-within less than 0.08 (Hu & Bentler, 1999), and SRMR-between less than 0.14 (Hsu et al, 2015).…”
Section: Data Analysesmentioning
confidence: 99%
“…One common approach to model evaluation uses fit indices (e.g., the root mean square error of approximation [RMSEA], comparative fit index [CFI], Tucker-Lewis index [TLI], and standardized root mean square residual [SRMR]) to assess the model fit. However, because a traditional MLGCM comprises both between and within models, it has been suggested that the models at different levels should be evaluated separately by level-specific fit indices (Hox, 2010;Hsu, Kwok, Acosta, & Lin, 2015;Ryu, 2014;Ryu & West, 2009). Studies contributing to understanding the performance of level-specific fit indices in MSEM have been conducted in the context of multilevel confirmatory factor analysis (MCFA; e.g., Hsu, Lin, Kwok, Acosta, & Willson, 2016;Ryu & West, 2009), multilevel path models (Ryu, 2014), and multilevel nonlinear models (Schermelleh-Engel, Kerwer, & Klein, 2014).…”
mentioning
confidence: 99%